Flow of non-starter lactic acid bacteria : from to silage to raw milk to cheese - Johansson, John (SLU/Department of Molecular Sciences, 2022)
Modern cheese manufacturing uses a known starter culture of lactic acid bacteria (SLAB) for the fermentation of lactose to lactic acid. There is, however, often a second fermentation in cheese manufacturing by non-starter lactic acid bacteria (NSLAB). These LAB are not added in the manufacturing, and it is not always clear where these LAB originate from. The main objective of this review was to study if there is a flow of NSLAB from silage to raw milk and to the resulting cheese. More specific objectives were to investigate how LAB in silage may affect the raw milk, if LAB stemming from silage can act as NSLAB in cheese, and if so, how they affect the cheese. L. plantarum, L. paracasei and L. casei were found to be the LAB most described as NSLAB in cheese, with the potential to persist in raw milk and occasionally survive pasteurisation. LAB in silage is crucial for the fermentation process, and NSLAB in cheese can enhance flavour of cheese but also cause defects during ripening. Most LAB from silage do not enter the milk, but some actually do. LAB in the milk could enter through other contamination sources but it possible that some LAB from silage survive and act as NSLAB in the cheese. More research is needed to confirm the flow of LAB in the value chain of milk and cheese.